Mobility Program: outbound student's exchange program to Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia - Norhidayah, Mohamad (2017)
FKKSA successfully sent five students abroad to join the student exchange program at the Chemical Engineering Department of Faculty of Industrial Technology, Institut Teknologi Sepuluh Nopember (ITS) in Surabaya, Indonesia. The students, Muhammad Syakir Bin Muhammad Salleh, Norfarahin Binti Hamzah, Nur Syazaarina Binti Ahmad, Khairunnisa Binti Kamarul Arifin and Fatin Fatihah Binti Emran, are undertaking the undergraduate studies for one semester starting from 26 August to 7 January 2018.